EFFECTIVENESS OF THE DEVELOPED EDUCATIONAL MEDIA ON THE POSTPARTUM CARE KNOWLEDGE ACCORDING TO THE THAI TRADITIONAL MEDICINE METHODS - Khongkhon, Somjet; Pisaipan, Ratchadaphorn; Sarakarn, Wadsana; Singhato, Alongkote (Srinakharinwirot University Journal of Sciences and Technology, 2022)
The Thai traditional medicine (TTM) is reported for its effectiveness on health promotion for postpartum women. Giving knowledge to pregnant women on the methods and benefits of TTM is important to make them awareness and interesting on this health care methods. Unfortunately, there is no accepted and effective educational media available in antenatal care unit of local hospitals in Thailand. This pre-experimental study aimed to investigate the effectiveness of the developed educational media on the methods and benefits of TTM. One-hundred of the first pregnant women who came to visit the Antenatal Care unit, Sunpasitthiprasong Hospital, Ubon Ratchathani province were convenience sampled to participate in this study. The study tools were the knowledge questionnaire on the methods and benefits of TTM and satisfaction questionnaire toward the developed educational media which were reviewed and validated by 3 experts. Results revealed that the participants’ average score on TTM knowledge after attending the developed educational media was significant higher than pre-test (p<0.05). In addition, the participants’ average knowledge scores were no significant difference between groups on education and income levels. Last, the average participants’ satisfaction scores indicated that they were satisfied on the developed educational media. In conclusion, the developed educational media on TTM was effective and acceptable to participants that can further use to educate pregnant women in antenatal care units.